2020
DOI: 10.3390/metabo10040145
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Fingerprinting with Fourier-Transform Infrared (FTIR) Spectroscopy: Towards a High-Throughput Screening Assay for Antibiotic Discovery and Mechanism-of-Action Elucidation

Abstract: The discovery of antibiotics has been slowing to a halt. Phenotypic screening is once again at the forefront of antibiotic discovery, yet Mechanism-Of-Action (MOA) identification is still a major bottleneck. As such, methods capable of MOA elucidation coupled with the high-throughput screening of whole cells are required now more than ever, for which Fourier-Transform Infrared (FTIR) spectroscopy is a promising metabolic fingerprinting technique. A high-throughput whole-cell FTIR spectroscopy-based bioassay wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 56 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…Since universally applicable methods for characterizing the MoA(s) of antibiotics do not exist, a full suite of expertise in genetics, genomics, microbiology, chemical biology and biophysics is required. Identification of the molecular target can be achieved by targeted screens of indicator or mutant strains, whole-genome sequencing upon focused resistance development 224 , 225 , pattern recognition techniques based on transcriptomics 226 , imaging 227 , 228 , metabolomics 229 , macromolecular synthesis 230 , 231 or mutant fitness profiles 232 , 233 , which can be coupled with machine learning approaches for directed predictions 225 , 233 , or chemoproteomics 234 , 235 . The latter is specifically useful in the case of non-essential target inhibitors like pathoblockers, since these may not generate resistant mutants (at least under standard laboratory conditions).…”
Section: Advancing Hits To (Pre)clinical Statusmentioning
confidence: 99%
“…Since universally applicable methods for characterizing the MoA(s) of antibiotics do not exist, a full suite of expertise in genetics, genomics, microbiology, chemical biology and biophysics is required. Identification of the molecular target can be achieved by targeted screens of indicator or mutant strains, whole-genome sequencing upon focused resistance development 224 , 225 , pattern recognition techniques based on transcriptomics 226 , imaging 227 , 228 , metabolomics 229 , macromolecular synthesis 230 , 231 or mutant fitness profiles 232 , 233 , which can be coupled with machine learning approaches for directed predictions 225 , 233 , or chemoproteomics 234 , 235 . The latter is specifically useful in the case of non-essential target inhibitors like pathoblockers, since these may not generate resistant mutants (at least under standard laboratory conditions).…”
Section: Advancing Hits To (Pre)clinical Statusmentioning
confidence: 99%
“…FTIRS has been shown to detect antibiotic‐induced profiles that elucidate their MOA (Huleihel et al, 2009; Ribeiro da Cunha et al, 2019, 2020; Xuan Nguyen et al, 2017). In addition to the prediction of both known and simulated novel MOA, we have shown that FTIRS can be used to estimate potency and to probe the gray chemical matter (Ribeiro da Cunha et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Fourier‐transform infrared (FTIR) spectroscopy (FTIRS) is a technique with such characteristics that reflects the vibrational energy of molecular bonds after their interaction with infrared radiation, thereby revealing the atoms participating in said bonds, which in turn conveys the molecular composition of biological samples regarding nucleic acids, proteins, carbohydrates, lipids, phospholipids, among others (Ribeiro da Cunha et al, 2020). FTIRS conveys the molecular composition of samples with sufficient detail that it is suitable for metabolic fingerprinting in general (Goodacre et al, 2004), and specifically for identifying antibiotic‐induced profiles (Huleihel et al, 2009; Ribeiro da Cunha et al, 2019, 2020; Xuan Nguyen et al, 2017). Recently, FTIRS has also been shown to be sufficiently sensitive for screening animal DNA polymorphism (Gomes Rios et al, 2021) as well as for detecting single mtDNA deletions, which can enable the diagnosis of mitochondrial myopathy in clinical practice (Gervasoni et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Because FTIRS has been underexplored but holds great potential, we dwelled into its application towards MOA identification. Firstly, we applied a macro-cultivation assay, from which it became clear that metabolic fingerprints reflect the MOA of antibiotics [ 102 ]. We then refined our assay into a high-throughput micro-cultivation protocol, from which we successfully predicted the MOA of antibiotics at the level of the major biosynthetic pathway, class, and individual antibiotics.…”
Section: Vibrational Spectroscopymentioning
confidence: 99%